Selective HIF stabilization alleviates hepatocellular steatosis and ballooning in a rodent model of 70% liver resection. Issue 19 (15th October 2021) - Iesari, Samuele; Leclercq, Isabelle; Joudiou, Nicolas; Komuta, Mina; Daumerie, Aurélie; Ambroise, Jérôme; Dili, Alexandra; Feza-Bingi, Natacha; Xhema, Daela; Bouzin, Caroline; Gallez, Bernard; Pisani, Francesco; et al.
Abstract: Background: Small-for-size syndrome (SFSS) looms over patients needing liver resection or living-donor transplantation. Hypoxia has been shown to be crucial for the successful outcome of liver resection in the very early postoperative phase. While poorly acceptable as such in real-world clinical practice, hypoxia responses can still be simulated by pharmacologically raising levels of its transducers, the hypoxia-inducible factors (HIFs). We aimed to assess the potential role of a selective inhibitor of HIF degradation in 70% hepatectomy (70%Hx). Methods: In a pilot study, we tested the required dose of roxadustat to stabilize liver HIF1α. We then performed 70%Hx in 8-week-old male Lewis rats and administered 25 mg/kg of roxadustat (RXD25) at the end of the procedure. Regeneration was assessed: ki67 and 5-ethynyl-2′-deoxyuridine (EdU) immunofluorescent labeling, and histological parameters. We also assessed liver function via a blood panel and functional gadoxetate-enhanced magnetic resonance imaging (MRI), up to 47 h after the procedure. Metabolic results were analyzed by means of RNA sequencing (RNAseq). Results: Roxadustat effectively increased early HIF1α transactivity. Liver function did not appear to be improved nor liver regeneration to be accelerated by the experimental compound. However, treated livers showed a mitigation in hepatocellular steatosis and ballooning, known markers of cellular stress after liver resection. RNAseq confirmed that roxadustat unexpectedly increases lipid breakdown and cellular respiration. Conclusions: Selective HIF stabilization did not result in an enhanced liver function after standard liver resection, but it induced interesting metabolic changes that are worth studying for their possible role in extended liver resections and fatty liver diseases.